OP0008 Single Center Experience in Next Generation Sequencing for Genetic Diagnosis of Autoinflammatory Disorders (AIDS). (9th June 2015) - Lepri, F.R.; Pisaneschi, E.; Minervino, D.; Messia, V.; Pardeo, M.; De Benedetti, F.; Insalaco, A.
Abstract : Background: Autoinflammatory disorders (AIDs) represent a group of complex diseases characterized by periodic or chronic systemic inflammations with involvement of various organs and systems in the absence of evidence of autoimmunity or infections. Mutations in more than 15 genes, affecting several distinct pathways, have been associated with autoinflammatory recessive/dominant syndromes [1]. The molecular genetic analysis of these diseases based just on the candidate gene has low efficiency and it's time consuming and expensive. Next Generation Sequencing (NGS) has emerged in the last year as new diagnostic tool in this field. Objectives: To share data obtained by the application of NGS in a cohort of patients affected by an AIDs of undefined origin evaluated at our center. Methods: In this study we enrolled 145 patients evaluated at our center from 2010 to 2014, affected by undefined AIDs. In order to improve variant detection, to reduce diagnosis time and to correlate phenotype of patients with their genotype on multiple genes, we developed NGS approaches starting with 11 genes (divided into two panels), already known to be involved in AID (Panel 1: MVK, MEFV, NRLP12, NRLP3, NOD2, TNFRSF1A and PSTPIP1 ; Panel 2: IL1RN, LPIN2, IL36RN, PSMB8). Targeted resequencing was performed using a uniquely customized panel and analyzed with the MiSeq® sequencing platform (Illumina, San Diego, CA). All variants identified have been confirmed by Sanger sequencing and, when possible, family members were tested to study the segregation of identified variants. Results: NGS analysis led to the identification of 61 patients with different variants in the genes of panel 1, with a detection rate of 42%. 36% of the patients showed variants in the NLRP3 gene, 19% in NOD2, 31% in NLRP12, 23% in MEFV, 8% in MVK and TNFRSF1A, 6% in PSTPIP1 . Some of these variants are novel and others are already known or polymorphisms. In 29% of patients the combination of variants in two different genes was found. Several variants are of unknown pathogenic significance, while some of them are described as risk factors. We performed 15 familial study to unravel the segregation of some variants. Conclusions: NGS leads to the identification of many genetic variants that could be associated with disease susceptibility. The major challenge is in the interpretation of the clinical relevance of identified variants, particularly of variants that are found at low, but >1%, frequency in various populations. These may function as susceptibility alleles to inflammation rather than disease-associated mutations [2]. Some patients show variants in multiple analyzed genes: it can be assumed that different variants in different genes may cooperate to determine a pathological phenotype.This will necessitate large-scale population studies, in vitro functional assay and careful correlation of genetic information with phenotypic data [3]. Crucial is close collaboration with clinicians. References: Martinon F, Aksentijevich I. New players driving inflammation in monogenic autoinflammatory diseases. Nat Rev Rheumatol 2015 Jan;11(1):11-20. Shinar Y, et al. Guidelines for the genetic diagnosis of hereditary recurrent fevers. Ann Rheum Dis 2012 Oct;71(10):1599-605. Aksentijevich I, Kastner D. Genetics of monogenic autoinflammatory diseases: past successes, future challenges. Nat Rev Rheumatol 2011 Jul 5;7(8):469-78. Disclosure of Interest: None declared